SIFAT KEPUTUSAN BADAN PENGAWAS PEMILIHAN UMUM DALAM PENYELESAIAN SENGKETA PEMILIHAN UMUM - Mia Siratni (Ensiklopedia of Journal, 2021)
Bawaslu resolves by deliberation by bringing together the disputing parties to then take a final and binding decision. The final and binding nature of this Bawaslu decision does not apply to certain disputes, namely the dispute over the verification of political parties participating in the General Election and the determination of the final list of candidates for the election of members of the DPR, DPD, and DPRD. The existence of these two characteristics of Bawaslu's decision then led to different interpretations between Bawaslu and the KPU. The formulation of the problem, namely 1). The authority of Bawaslu in resolving election disputes regarding the task of supervising the implementation of elections, 2). The nature of Bawaslu's decisions in resolving election disputes. The research method used in this paper is normative juridical, namely an approach to legal norms or applicable laws and regulations, theories, and history. From the discussion of the problem, it is concluded that a decision that is final and binding is given to Bawaslu by law in order to end election disputes so that it will show the role of Bawaslu as a unified function of organizing elections. Meanwhile, exceptions to the nature of final and binding decisions on political party verification disputes and the permanent list of candidates for members of the DPR, DPD, and DPRD indicate that Bawaslu is not a judicial institution, so it cannot decide disputes related to constitutional rights as election participants.